2002
DOI: 10.1055/s-2002-34115
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Opiate Addicts with Multiple Drug Abuse: a Comparison of Buprenorphine vs. Methadone

Abstract: Over the last few years, there has been a growing tendency for opioid addicts to abuse multiple drugs, although many patients are in substitution therapy with methadone. Abuse of multiple drugs leads to a more complicated withdrawal syndrome; it is therefore necessary to investigate new drug strategies as a treatment for detoxification. Buprenorphine appears to be an effective and safe drug in opioid-addicted patient detoxification. In this study, we have compared the short-term efficacy of an 11-day low-dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
2
26
0
1
Order By: Relevance
“…The highest levels of opiate withdrawal found in the multiple substance disorder group (MSD) lead to hypothesize that the primary dependence in MSD subjects was more severe than the correspondent dependence on the single substance, so that subthreshold symptoms of protracted withdrawal could still be detected in them by rating. It is in fact known that the abuse of multiple substances is associated with a more complicated and sustained withdrawal syndrome [47] .…”
Section: Discussionmentioning
confidence: 99%
“…The highest levels of opiate withdrawal found in the multiple substance disorder group (MSD) lead to hypothesize that the primary dependence in MSD subjects was more severe than the correspondent dependence on the single substance, so that subthreshold symptoms of protracted withdrawal could still be detected in them by rating. It is in fact known that the abuse of multiple substances is associated with a more complicated and sustained withdrawal syndrome [47] .…”
Section: Discussionmentioning
confidence: 99%
“…The authors are aware of only six published studies. [20][21][22][23][24][25] A Cochrane Review of buprenorphine detoxification and maintenance studies concluded that completion of withdrawal treatment is possibly more likely when managed with buprenorphine compared to methadone. 26 However, the difference was not statistically significant and no data were reported on post-detoxification outcomes, leading the authors to conclude that more research was needed to evaluate possible differences in effectiveness between the two medications.…”
Section: Methodsmentioning
confidence: 99%
“…26 Only three studies had a primary outcome of abstinence from opiates evidenced by biochemical urine sample. 20,21,24 Only two studies used comparative statistics and one acknowledged small sample size as a limitation that affected significance. Both community-based studies demonstrated no significant difference between buprenorphine and methadone, for either abstinence 20 or retention in drug treatment.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Dose reduction of buprenorphine appears to be associated with less severe withdrawal effects than withdrawal from methadone, whereas a switch to buprenorphine can be more problematic than initiation of treatment with methadone. 11,12 However, the effects of the 2 drugs on the circadian rhythm have still not been sufficiently investigated. Although there are some data on the effects of acute administration of opioids on sleep architecture in healthy adults, 13 little is known of the effects on sleep in chronic users during opioid detoxification.…”
mentioning
confidence: 99%